Pengaruh Sinetron Ikatan Cinta Terhadap Perilaku Remaja: Survei pada Remaja RT 008/012 Kedaung, Pamulang, Tangerang Selatan - Ibnu Satrio Wibowo; Fal Harmonis (Jurnal Kajian dan Penelitian Umum, 2024)
Ikatan Cinta became one of the most influential soap operas with very high ratings. The soap opera Ikatan Cinta raises the story of romance, family, and social issues that occur in society. This soap opera has an influence that is considered quite large in society, especially in the teenage community. This study aims to determine the effect of the soap opera Ikatan Cinta on Teenage Behavior (Survey on Teenagers of RT 008 RW 012 Kedaung, Pamulang, South Tangerang). This research uses quantitative method by conducting a survey on 50 teenagers in RT 008 RW 012 Kedaung, Pamulang, South Tangerang. The data analysis used in this research is simple linear data analysis with two variables, namely Sinetron Ikatan Cinta as the independent variable and Teen Behavior as the dependent variable. The results of this study indicate a very strong and significant correlation between the influence of Love Bond soap operas on Teenage Behavior with a correlation coefficient of 0.824. The results of hypothesis testing show that the thiitung value is 10.0757893> 1.67722 ttabel, so Ho is rejected and Ha is accepted, meaning that there is a significant influence between the influence of the Love Bond soap opera on Teen Behavior.